2022
DOI: 10.1038/s41531-022-00366-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced synaptic activity and dysregulated extracellular matrix pathways in midbrain neurons from Parkinson’s disease patients

Abstract: Several mutations that cause Parkinson’s disease (PD) have been identified over the past decade. These account for 15–25% of PD cases; the rest of the cases are considered sporadic. Currently, it is accepted that PD is not a single monolithic disease but rather a constellation of diseases with some common phenotypes. While rodent models exist for some of the PD-causing mutations, research on the sporadic forms of PD is lagging due to a lack of cellular models. In our study, we differentiated PD patient-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 105 publications
12
46
0
Order By: Relevance
“…These results suggested that PGC-1α in astrocytes might act as an endogenous protective mechanism in AIS patients (Tu et al, 2021). PGC-1α is also involved in regulating the glutathione system of astrocytes, which in turn reduces the oxidative and metabolic damage (Stern et al, 2022). Considering these neuroprotective effects of PGC-1α, regulating the level of PGC-1α could be a promising neuroprotective strategy (Savini et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…These results suggested that PGC-1α in astrocytes might act as an endogenous protective mechanism in AIS patients (Tu et al, 2021). PGC-1α is also involved in regulating the glutathione system of astrocytes, which in turn reduces the oxidative and metabolic damage (Stern et al, 2022). Considering these neuroprotective effects of PGC-1α, regulating the level of PGC-1α could be a promising neuroprotective strategy (Savini et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…Almost nothing is known about the electrophysiological activities and Ca 2+ homeostatic processes in the emerging mDA neurons, most likely playing a role already during the earliest stages of mDA neuron development and long before they have established a proper connectivity with their efferent and afferent targets, although their mitochondrial energy metabolism and autophagic/lysosomal clearance of misfolded proteins and defective organelles are now beginning to be unraveled in the human context in vitro ( section 3.1.2 ). This fact has probably led to a collective neglect of these aspects arguing that they might not be biologically relevant, although several evidences have meanwhile accumulated suggesting the opposite is true for the developing mammalian VM and mDA neurons, both in the wildtype and in the PD context ( Chan et al, 2007 ; Rockhill et al, 2009 ; Ferrari et al, 2012 ; Ramirez-Latorre, 2012 ; Kim et al, 2020 ; Carola et al, 2021 ; Akrioti et al, 2022 ; Stern et al, 2022 ; Virdi et al, 2022 ). It has been suggested that such ion- and neurotransmitter-driven early (immature) activities in developing neurons represent “phenotypic checkpoints” integrating intrinsic TF-mediated (genetic) developmental pathways with extrinsic signals from the surrounding environment to ensure the overall correct establishment of a neuron’s identity and function in the broader context of the nervous system ( Ben-Ari and Spitzer, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This link between mRNA translation is poorly understood, but a few reviews have highlighted that restoring translation and proteostasis might be a useful target for new therapeutics ( Correddu and Leung, 2019 ; Zhou et al, 2019 ). Impaired proteostasis at the synapse could also be important for PD ( Nachman and Verstreken, 2022 ) while reduced synaptic activity and dysregulated extracellular matrix pathways have recently been reported in midbrain neurons from PD patients, providing evidence that synaptopathy is a general phenotype in PD ( Stern et al, 2022 ). Thus, biological processes related to the ribosome, translation, and tRNA, specifically at the synapse, could possibly be an important molecular mechanism in PD pathobiology.…”
Section: Discussionmentioning
confidence: 99%